Analysis of the Management of Sports Facilities and Infrastructure at the UPTD Kebatakan Sports of West Sumatra Province - Febrianti Eka Putri; Nugroho Susanto; Yogi Andria (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The increase in sports achievements obtained by West Sumatra Province was influenced by many factors, one of which was the sports facilities and infrastructure at the UPTD of West Sumatra Province's Talent Sports. The aim of the study was to find out how the management of sports facilities and infrastructure at the UPTD Kebatakan Sports of West Sumatra Province can increase achievement. The method used in this research is the descriptive-qualitative method. Sources of research data are the management of sports facilities and infrastructure and documentation. The results of the study show that the completeness of the management of facilities and infrastructure at the UPTD of Sports Talent in the Province of West Sumatra is a factor in increasing achievement. planning in collaboration with the government of West Sumatra Province. Organising (organizing), which is directly led by the manager, preparation of personnel (staffing) according to employee recruitment standards, directing (directing), which is carried out directly by the manager, and supervision (controlling) are carried out at any time. The conclusion in this study is that the management of sports facilities and infrastructure at the UPTD of Sports Talent in the Province of West Sumatra in improving sports achievement in the Province of West Sumatra is a supporting factor for the positive outcome of the event. It is recommended to add sports facilities and infrastructure, such as rubber jogging tracks, and improve the organisational system according to the sports sector.